Predominant gut Lactobacillus murinus strain mediates anti-inflammaging effects in calorie-restricted mice - Pan, Fengwei (Microbiome, 2018)
BACKGROUND: Calorie restriction (CR), which has a potent anti-inflammaging effect, has been demonstrated to induce dramatic changes in the gut microbiota. Whether the modulated gut microbiota contributes to the attenuation of inflammation during CR is unknown, as are the members of the microbial community that may be key mediators of this process. RESULTS: Here, we report that a unique Lactobacillus-predominated microbial community was rapidly attained in mice within 2 weeks of CR, which decreased the levels of circulating microbial antigens and systemic inflammatory markers such as tumour necrosis factor alpha (TNF-α). Lactobacillus murinus CR147, an isolate in the most abundant operational taxonomic unit (OTU) enriched by CR, downregulated interleukin-8 production in TNF-α-stimulated Caco-2 cells and significantly increased the lifespan and the brood size of the nematode Caenorhabditis elegans. In gnotobiotic mice colonized with the gut microbiota from old mice, this strain decreased their intestinal permeability and serum endotoxin load, consequently attenuating the inflammation induced by the old microbiota. CONCLUSIONS: Our study demonstrated that a strain of Lactobacillus murinus was promoted in CR mice and causatively contributed to the attenuation of ageing-associated inflammation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40168-018-0440-5) contains supplementary material, which is available to authorized users.